The Influence of Motivation, Compensation and Work Stress on Employee Performance at PT. BANK SUMUT Pusat Medan - Nurul Fadhillah; Muhammad Toyib Daulay (International Journal of Scientific Multidisciplinary Research, 2024)
This study uses a quantitative method to assess motivation, compensation, and work stress affect employees' performance at PT Bank Sumut Medan. Observation and questionnaires were used to gather data, which was then analyzed using multiple linear regression analysis techniques with SPSS version 25. 40 PT Bank Sumut Medan personnel made up the research sample. The study's findings suggest that, to a partially positive and considerable extent, motivation, compensation, and work stress all affect employee performance. Additionally, all three of these factors work together to significantly and favorably impact employee performance